Fish Pathogenic Bacteria (Aeromonas Hydrophilia) Induced Histopathological Attributes in the Spleen and Lymph-Nodes of Swiss Albino Mice - Pramanik, AK; Santra, KB (Bangladesh Journal of Scientific and Industrial Research, 2012)
The effect of fish pathogenic bacteria, Aeromonas hydrophilia on the spleen and lymph-nodes of male Swiss albino mice has been investigated and examined histopathologically. Morphological and histological changes on the 7th, 14th, 21st, and 30th day of infection were noticed. Time exposure showed no significant difference in body weight between control and treated mice but the value showed a tendency towards increment. Spleen weight was increased significantly (p < 0.001) at 14th and 21 st days of post treated mice. The treatment groups showed hepatocellular necrosis of spleen and other immuno- responsive tissue like lymph-node of mice also. The damaging nature of the immuno-responsive tissues of mice to the pathogenesis of bacteria, Aeromonas hydrophilia is provoked in the results obtained.